PARADOXICAL POSTMODERN ELEMENTS IN THE SELECT TEXTS OF ALEJO CARPENTIER, MARLON JAMES AND GABRIEL GARCIS MARQUEZ - Imsong, I. Talisenla; Pongen, Rongsennungla (ShodhKosh: Journal of Visual and Performing Arts, 2022)
‘Paradox’ refers to a proposition with contradictory features, ambiguous, mystical, irrational and inconsistent qualities that juxtaposition together. The essence of Caribbean literature encapsulate black humour, paradox, decentralisation and rebellion against economic capitalism dealing with a wide range of themes that concerns Caribbean historical experience of slave labour, migration, ethnicity, resistance and language. Caribbean literature emerged from the territories of the Caribbean region and is used interchangeably with West Indies Literature despite having different origins, and refer to slightly different groups of people. The West Indian refers to those settlers in the Caribbean islands of “European origin and of people of African origin brought to the area as slaves; Caribbean, on the other hand, refers to the people and culture of the Caribbean. The emergence of West Indies Literature began as V.S Naipaul, George Lamming, Samuel Selvon etc published in the UK. The literature, culture is shaped by the diversity of people in race, language, colonialism, slavery and so forth signifying an evolution towards postmodernism- a broad movement that was popularized in the mid to late twentieth Century, marking its departure from modernism. Jean Francois Lyotard (1984 24) on postmodernism illustrates skepticism on universalizing theories, “I define postmodern as incredulity towards metanarratives'' emphasising on local narratives as an approach to understand political and social transformation. Foucault (1984 34-38) also dismisses modernism's precursor, The Enlightenment theory, which characterizes his postmodernity. Postmodern theory rejects totalizing and universalizing truth and knowledge, the myth of enlightenment as the path to progress. Post modernisms’ objection to objectivity has created a conundrum and multiperspective point of view in various scopes of literature, architecture, science and ethics etc. The authors selected for this study are Alejo Carpentier (December 26,1904-April 24, 1980), Gabriel Marquez (March 6,1927-April17, 2014), and Marlon James (November 24, 1970- ), established writers of Caribbean origin. Carpentier is a Cuban novelist Essayist that greatly influenced Latin American Literature. He explored the Latin American history and culture, and was among the first to use magical realism- the most famous example of Afro-Cuban influence is the novel The Kingdom of This World. Gabriel Garcia Marquez is a Colombian novelist, one of the most significant authors especially in Spanish Language. He is known for popularising Magic Realism and was conferred the prestigious Nobel Prize in literature in 1982. Marlon James is the first Jamaican author to receive the Man Booker Prize for the novel A Brief History of Seven Kingdoms published in 2015. He is also a recipient of the 2010 Dayton Literary Peace Prize and Minnesota Book award for his novel The Book of Night Women.